DESIGN AND ANALYSIS OF A HIGH FREQUENCY RESONANT SEPIC BIDIRECTIONAL CONVERTER AND THE ASSOCIATED BATTERY MODELING FOR BATTERY EQUALIZATION APPLICTATIONS - Florencki, Timothy (My University, 2013)
In this thesis, a high frequency resonant SEPIC bidirectional converter is proposed that has applications in battery equalization and charging/discharging. Motivations and applications for battery equalization are explored. Previous work on battery equalization is presented, and the benefits and challenges of high frequency power electronics are explored. The proposed high frequency converter is small in size due to reduced size of the magnetic components. The design, simulation, and experimental procedure is outlined. Experimental results show that the efficiency is greater than 81%. Ways to improve the efficiency are also explored and mentioned. This thesis also presents a new electrical circuit topology that can be used to accurately model batteries. The proposed model has only two circuit components, making it very simple when compared to some of the popular battery models used today. Also, the method to formulate the nonlinear component values that vary based on the current state of the battery is very straightforward because no optimization software or long battery tests are required. In this thesis, the new battery model is proposed and its performance is compared with that of the four most common electrical circuit battery models that are used today. Model formulation and the required battery testing is also detailed and explained. It is shown that the performance of the proposed model exceeds that of the common models. The work of this thesis can be seen as a contribution toward improving the current state of battery management systems (BMS). Batteries are fragile and complex systems that need careful management in order for battery technology to be usable and sustainable. It is believed that this thesis laid some of the groundwork necessary to improve current BMS. The modeling will help predict and monitor battery performance. The implementation of a RF DC-DC converter will decrease the size, improve the possibilities of power electronic integration with battery cells, and decrease the cost.
Keywords: high frequency; SEPIC converter; battery equalizer; resonant DC-DC converter; zero voltage switching; lithium-ion; electrical model; batteries